2x-(5x-6)=7+(x-1) 3x-1=2х-(4-х) 5х-(2х-9)=6+(х+3) 7х-8=4х-(1-3х) решить

Bekzhan20031 Bekzhan20031    2   04.10.2019 21:30    2

Ответы
mrgebil mrgebil  09.10.2020 20:29
2х-(5х-6)=7+(х-1)
2х-5х+6=7+х-1
2х-5х-х=7-1-6
-4х=0
не имеет корней

3х-1=2х-(4-х)
3х-1=2х-4+х
3х-2х-х=-4+1
0=-3
не имеет корней
ПОКАЗАТЬ ОТВЕТЫ
Linka00128 Linka00128  09.10.2020 20:29

1) 2x-5x+6=7+x-1

  -3x+6=x+6

  -3x+6-x-6=0

  -4x=0

   x=0/(-4)

   x=0

2) 3x-1=2x-4+x

   3x-1=3x-4

   3x-1-3x+4=0

   3≠0 не имеет корней

3) 5x-2x+9=6+x+3

   3x+9=x+9

   3x+9-x-9=0

   2x=0

   x=0/2

   x=0

4) 7x-8=4x-1+3x

   7x-8=7x-1

   7x-8-7x+1=0

   -7≠0 не имеет корней

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра